A15 EFFICACY AND SAFETY OF FILGOTINIB AS INDUCTION THERAPY FOR PATIENTS WITH MODERATELY TO SEVERELY ACTIVE ULCERATIVE COLITIS: RESULTS FROM THE PHASE 2B/3 SELECTION STUDY. (4th March 2021) - Feagan, B G; Loftus, E V; Danese, S; Vermeire, S; Sandborn, W J; Ritter, T; Mehta, R; Seidler, U; Seibold, F; Beales, I; Kim, H; McNally, J; et al.
Abstract: Aims: The SELECTION (NCT02914522) Induction Studies evaluated the efficacy/safety of filgotinib (FIL), a preferential JAK1 inhibitor, as induction therapy for patients (pts) with moderately to severely active ulcerative colitis (UC) who were biologic-naïve but failed conventional therapy (Induction Study A) or failed prior biologics (Induction Study B). Methods: Pts were randomized 2:2:1 to once–daily FIL 200mg, FIL 100mg or placebo (PBO). The primary (clinical remission), key secondary (Mayo Clinic Score [MCS] remission, endoscopic remission, and histologic remission), and exploratory endpoints (MCS response and endoscopic improvement) were assessed at Week 10. Results: In both studies, baseline demographics and disease characteristics were similar across treatment groups. In Study A, 659 pts were randomized and treated. Baseline mean MCS was 8.6 and 56% had a Mayo endoscopic subscore (ES)=3. A significantly higher proportion of biologic-naïve pts on FIL 200mg achieved clinical remission vs PBO and all key secondary endpoints (Table). In Study B, 689 pts were randomized and treated. Baseline mean MCS was 9.3 and 78% had ES=3. Prior treatment failures were: anti-TNF (86%), vedolizumab (52%) and both (dual-refractory; 43%). A significantly higher proportion of biologic-experienced pts on FIL 200mg achieved clinical remission vs PBO. In Studies A and B, a greater proportion of pts on FIL 200 mg achieved an MCS response and endoscopic improvement vs PBO. The rates of AEs, serious AEs and discontinuations due to AEs were similar across FIL and PBO groups during induction. In the PBO, FIL 100mg and FIL 200mg groups, serious infections occurred in 0.7%, 0.7% and 0.4% pts in Study A and 1.4%, 1.4% and 0.8% pts in Study B; H Zoster occurred in <1% in both groups for both cohorts. Conclusions: SELECTION included a high proportion of dual-refractory pts, and pts with severe endoscopic disease. Both doses of FIL were well tolerated. Filgotinib 200mg was effective induction therapy for both biologic-naïve/-experienced pts with moderately to severely active UC. Funding Agencies: None